Transparency in Foreign Land Acquisitions: The role of institutions and information. (29th October 2019) - Scoppola, Margherita; Prontera, Andrea
Abstract: Motivation: Foreign land acquisitions (FLA) is a hot issue in development policy, but empirical work is scant, mostly because of the lack of official and consistent cross‐country data. Although transparency is a necessary ingredient to avoid FLA's most negative effects, no articles currently address this issue. Purpose: We examine transparency in the release of information on FLA by (a) measuring the degree of government transparency; (b) exploring the extent to which transparency depends upon democratic and governance features; and (c) discussing how the dissemination of information by non‐state actors can positively affect data disclosure. Approach and methods: First, we check the information source (including companies, non‐government organizations (NGOs) and research) and then compute an original index of transparency and the free flow of information on FLA for 78 countries. Finally, we discuss the relationship between transparency, free flow of information on FLA and political and institutional variables in the host country. Findings: With regional variations, institutional quality, democracy and the free flow of information overall are positively related to government transparency on FLA. Countries with a higher degree of information disseminated by non‐state actors tend to have higher data disclosure on FLA. The system of land governance contributes to explaining counter‐intuitive behaviour at the country level. Policy implications: The role of NGOs, research institutions and companies in providing information on FLA can contribute to improving government transparency. Researchers and activists emerge as important agents of change, especially when civil and political rights are restricted and local communities disempowered. Activists can help research on land governance by collecting data; the data disseminated by researchers can affect government transparency and improve land governance and development.